2018
DOI: 10.2174/1874467208666161128152518
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone Decreases Intracellular pH and Sensitizes Melanoma Cell Line A375 to Dacarbazin. Comparison with Acetazolamide

Abstract: We have demonstrated that inhibitors modify intracellular pH and CAIX functionality and sensitize cells to Dacarbazin. These original results complete the knowledge on Sulfamide CA IX inhibitors, bring new insights about Coumarin compounds and offer new possibilities in high grade melanoma therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Furthermore, this isoform serves as a driving force in cytosolic pH regulation . It has been reported that the resting intracellular pH of cells is affected by CA inhibitors, and this change varies depending on the cell type. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this isoform serves as a driving force in cytosolic pH regulation . It has been reported that the resting intracellular pH of cells is affected by CA inhibitors, and this change varies depending on the cell type. …”
Section: Resultsmentioning
confidence: 99%
“…Human carbonic anhydrases (EC 4.2.1.1) types IX and XII are overexpressed in a variety of cancer types and play a large role in pH regulation required to drive metastasis and growth, with greater importance to solid hypoxic tumors (54). Drugs such as CAIX inhibitor FC16-670A or any other compound that can down-regulate carbonic anhydrases will inevitably reduce the capacity of tumor cells to maintain acid-base equilibrium and thereby deal a vital blow to cancer survival, growth and resistance (e.g., sulfamides (acetazolamide) and coumarins (umbelliferon)) (55,56). Combined efficacy of chemotherapy drug treatment is greater when combined with an inhibitor of carbonic acids, proton pumps (57), or HDACs (58), all of which could reduce tumor acidity.…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer cell lines express a number of CAs, including transmembrane hCAIX, hCAXII, and cytosolic hCAII under hypoxic conditions and these CAs play vital roles in manipulating the pH i of cancer cells, thus promoting the growth and metathesis of tumors. According to previous studies, inhibition of CAs can lead to cellular pH i manipulation, which is a cell-type dependent effect. …”
Section: Resultsmentioning
confidence: 98%